The competitive advantage in business, capabilities and strategy: What general performance factors are found in the Spanish wine industry? - Juan Ramón Ferrer Lorenzo; María Teresa Maza Rubio; Silvia Abella Garcés (Wine Economics and Policy, 2018)
The wine sector in Europe has undergone a major change of trend in recent years, especially in Spain. On the one hand, the surface area has been reduced, but the production has been maintained by restructurings and improvements made in exploitation techniques. On the other hand, consumption has diminished causing a significant increase in competition. The Spanish wine sector is formed mainly by small and medium-sized firm, which is representative of the size of existing companies in Europe. This article aims to analyze the relationships between the competitive strategy, resources and capabilities of the firms, analyzing their technological and managerial capabilities, with business performance. 339 companies of the wine sector in Spain have been studied, differentiating between individual firms, cooperatives and mercantile companies. The results reveal that resources and capabilities along with strategies define competitive advantage, but their relationship and importance is different for each type of company.
Keywords: 330; Competitive advantage; Resource based view; Strategy; Wine industry